Digital signal processor system for motion sensor monitoring device - Liu, Tianlei (2018)
With the progression of semiconductor and integrated circuit industry, a significantly increasing number of system on chip (SOC) related applications are widely developed in various areas. This final year project (FYP) is a typical example of biomedical IC design application, especially intended for diabetic patients to monitor their body pressures such as foot pressure. Feet ulcer is a common symptom for terminal diabetic patients and usually causes serious problems. Most medical reports related to the disease of diabetes have pointed out that the nervous system of feet is often weaken for diabetic individual and as a result they will lose the tactile sense, either partially or totally. To avoid such damages to feet, the work of this project is intended to provide warnings to diabetic patients by measuring the real-time foot pressures with pressure sensor array implemented on socks. Precisely speaking, this project includes two major parts. In the first part, signals from pressure sensor array could be conveyed to a user terminal on time by passing through a series of electronic modules such as amplifiers, Analog to digital conversions (ADC) and so on. In the second part, in-device analysis about their motion activity was performed based on some concepts of machine learning, which can relate the real-time feet pressure values to different motion activities like walking or jogging. These two parts will work together to continuously generate the real-time foot pressure values of the user and give appropriate feedback under different scenarios of motion activities. In summary, this FYP will be beneficial to diabetic patients by helping them to avoid large abnormal pressures occurred on feet. Novel wearable product was designed in the end at low cost and it has large potential market prospect.